PRODUKSI COOKIES BLONDO SEBAGAI MAKANAN KONSUMSI TAMBAHAN DALAM UPAYA PENCEGAHAN STUNTING DI DESA TENIGA - Yadnya, Made Sutha; Amilia , Serlyana; Irawan , Aditia; Putra, Doddy Setya Darsanti; Jannah, Miftahul; Shahab, Seha; Noviana , Ena; Sukmawati, Sukmawati; Fiandra, Naufal Nanda; Nujulia, Nilti Haeratun; Solihati, Solihati (Universitas Mataram, 2024)
Teniga Village is one of the villages with coconut plantation potential in North Lombok Regency. Currently, Teniga village itself is faced with the problem of stunting. Responding to the challenge of stunting, which is a significant health problem in Teniga Village, the KKN-PMD team from Mataram University conducted an innovation project to utilize